2009
DOI: 10.1590/s0102-33062009000400002
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia de estípulas e coléteres de Psychotria carthagenensis Jacq. (Rubiaceae)

Abstract: Acta bot. bras. 23(4): 923-928. 2009 Introdução Nas Américas, a família Rubiaceae está representada por 229 gêneros e 5200 espécies (Delprete 1999), dentre elas Psychotria carthagenensis Jacq. com distribuição desde a Costa Rica até a Argentina; no Brasil ocorre do Pará ao Rio Grande do Sul (Delprete et al. 2005).Psychotria carthagenensis é encontrada em ambientes bastante distintos . De acordo com estes autores, no Sul do Brasil, a espécie ocorre desde o nível do mar até 600 m de altitude, em três tipologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
4
23
0
1
Order By: Relevance
“…The absence of vascularization observed in the colleters of M. obtusifolia has also been reported for other species of Gentianaceae (Renobales et al 2001;Delgado et al 2011;Dalvi et al 2013) and for other families of angiosperms (Appezzato-da-Glória and Estelita 2000; Paiva and Machado 2006;De-Paula and Oliveira 2007;Vitarelli and Santos 2009). Although Carlquist (1969) reported that vascularization is directly related to the size of the structure and not the developmental stage, this statement does not seem valid for the Gentianaceae, because although the colleters of Macrocarpaea are larger than the foliar colleters of other species of the same family, these are not vascularized.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The absence of vascularization observed in the colleters of M. obtusifolia has also been reported for other species of Gentianaceae (Renobales et al 2001;Delgado et al 2011;Dalvi et al 2013) and for other families of angiosperms (Appezzato-da-Glória and Estelita 2000; Paiva and Machado 2006;De-Paula and Oliveira 2007;Vitarelli and Santos 2009). Although Carlquist (1969) reported that vascularization is directly related to the size of the structure and not the developmental stage, this statement does not seem valid for the Gentianaceae, because although the colleters of Macrocarpaea are larger than the foliar colleters of other species of the same family, these are not vascularized.…”
Section: Discussionsupporting
confidence: 71%
“…In M. obtusifolia, colleters remain intact after the secretory phase, which suggests that the secretion is eliminated by cuticle pores (Vitarelli and Santos 2009). Furthermore, ultrastructural studies are necessary for clarifying the mechanism of elimination of colleter secretion in M. obtusifolia.…”
Section: Discussionmentioning
confidence: 99%
“…Standard type colleters are comprised of a secretory palisade epidermis covering a non-secretory central axis, which may or may not be vascularized with xylem and phloem (Lersten 1974). In contrast to this standard type of colleter, which has been described for other botanical families (Appezzato-da-Glória & Estelita 2000;Paiva & Machado 2006a;Vitarelli & Santos 2009), the most common type of colleter for the genus Chamaecrista, as shown by our data along with data provided by Coutinho et al (2015), are comprised of homogenous cells.…”
Section: Discussionmentioning
confidence: 50%
“…Chamaecrista and Caliciopsis studied, non-vascularized colleters have bee previously reported for other species of Chamaecrista belonging to other sections (De-Paula & Oliveira 2007;Coutinho et al 2013;, other species of Caesalpinioideae (Paiva & Machado 2006b;Paiva 2009;Souza 2014), and even species of other families (Paiva & Machado 2006a;Paiva 2009;Vitarelli & Santos 2009;Silva et al 2012;Dalvi et al 2013). Anatomically, the colleters described for the species of sect.…”
Section: Discussionmentioning
confidence: 72%
“…they can occur at adaxial surface or at margins; and it is possible to notice at calyx, close to trichomes (majumdar & pal 1958, horner & lersten 1968, lersten 1974a, b, miller et al 1983, Robbrecht 1988, thomas 1991, da Cunha & Vieira 1997, Klein et al 2004, miguel et al 2006, Vitarelli & santos 2009. Rubiaceae colleters show little morphological variation comparing to literature, however, there is a great diversity of length, form and development of a basal constriction, and central axis diameter (Robbrecht 1988).…”
Section: Introductionmentioning
confidence: 99%